2016
DOI: 10.1371/journal.pone.0166234
|View full text |Cite
|
Sign up to set email alerts
|

Inferring Gene Networks for Strains of Dehalococcoides Highlights Conserved Relationships between Genes Encoding Core Catabolic and Cell-Wall Structural Proteins

Abstract: The interpretation of high-throughput gene expression data for non-model microorganisms remains obscured because of the high fraction of hypothetical genes and the limited number of methods for the robust inference of gene networks. Therefore, to elucidate gene-gene and gene-condition linkages in the bioremediation-important genus Dehalococcoides, we applied a Bayesian inference strategy called Reverse Engineering/Forward Simulation (REFS™) on transcriptomic data collected from two organohalide-respiring commu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…Although the exact function of the Fdh-like oxidoreductase in D. mccartyi remains unknown, protein analysis of D. mccartyi strain CBDB1 suggested it is involved in the enzyme complexes that are critical to the electron transport chain of the D. mccartyi species (Kublik, et al 2016;Türkowsky et al 2018). In our study, the expression levels of fdh (DET0186-DET 0187) in both ANAS and CANAS were found to be at similar levels to the hydrogenases hup, hym, and vhu (Supplemental material Table S4), consistent with the previous findings (Mansfeldt et al 2014, Mansfeldt et al 2016, Heavner et al 2018.…”
Section: Transcriptional Analysissupporting
confidence: 91%
See 1 more Smart Citation
“…Although the exact function of the Fdh-like oxidoreductase in D. mccartyi remains unknown, protein analysis of D. mccartyi strain CBDB1 suggested it is involved in the enzyme complexes that are critical to the electron transport chain of the D. mccartyi species (Kublik, et al 2016;Türkowsky et al 2018). In our study, the expression levels of fdh (DET0186-DET 0187) in both ANAS and CANAS were found to be at similar levels to the hydrogenases hup, hym, and vhu (Supplemental material Table S4), consistent with the previous findings (Mansfeldt et al 2014, Mansfeldt et al 2016, Heavner et al 2018.…”
Section: Transcriptional Analysissupporting
confidence: 91%
“…However, a recent transcriptomic study revealed that DET0187 was expressed at similar levels to the Hup subunit (DET 0112) in multiple D.mccartyi strains (Mansfeldt et al 2014). The Fdh-like oxidoreductase (DET0187) was shown to be associated with the Fdh-like protein DET0112 from the hup operon (Mansfeldt et al 2014) and a recent transcriptomic study of D. mccartyi-containing microbial communities indicated the expression pattern of the Hup and the Fdh-like oxidoreductase are strongly linked (Mansfeldt et al 2016). Although the exact function of the Fdh-like oxidoreductase in D. mccartyi remains unknown, protein analysis of D. mccartyi strain CBDB1 suggested it is involved in the enzyme complexes that are critical to the electron transport chain of the D. mccartyi species (Kublik, et al 2016;Türkowsky et al 2018).…”
Section: Transcriptional Analysismentioning
confidence: 99%
“…Additionally there was strong evidence for expression of the formate-dehydrogenase like (“Fdh”-like) oxidoreductase (NSAF = 4.62 × 10 −3 for the alpha subunit). Although the exact function of “Fdh” in DMC remains unknown, this oxidoreductase is proposed to be involved in enzyme complexes critical to DMC’s electron transport chain [ 29 , 37 ]. With respect to the high expression levels of respiratory enzymes in DMC these protein abundance findings agreed with previously published omics datasets [ 28 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…Continuous TCE feed experiments were conducted as 100 mL subcultures of undiluted KB-1 TM culture with 60 mL of anaerobic headspace in 160 mL, anaerobic serum bottles as described previously [ 22 , 37 ]. Parameters for the experiments are presented in Table S1 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation